Musical Hallucinations and Forgotten Tunes – Case Report and Brief Literature Review - Vitorovic, Danilo; Biller, Jose (Frontiers in Neurology, 2013)
Musical hallucinations represent a specific form of auditory hallucinations whereby patients experience formed music without an external source. We describe a 60-year-old woman with history of bilateral hearing impairment and tinnitus who experienced both recognizable and non-recognizable songs. Curiously, she was able to reproduce non-recognizable songs in a way that could be recognized by others. This phenomenon is in line with current understanding that musical hallucinations represent abnormal activity in the auditory associative cortices, raising intriguing questions regarding memory, forgetting, and access to lost memories.